Parasitizations Levels and Temperature Tolerance of Rice Bug (Leptocorisa oratorius Fabricius) Egg Parasitoids: Mass Rearing for Biological Control - Maulina, Fri; Nelly, Novri; Hidrayani, Hidrayani; Hamid, Hasmiandy (International Journal on Advanced Science, Engineering and Information Technology, 2018)
The rice bug is a significant pest that attacks wet rice fields Rice bug egg parasitoids can be used as a biological control for this pest in the field. Successful parasitoid mass rearing in the laboratory depends on optimum temperatures to ensure the fitness of the adults that are introduced into the field. The objectives of this research were to determine the parasitization levels of rice bug egg parasitoids from two areas in West Pasaman Regency; one in the lowlands (Kinali 56 m asl) and the one at a higher altitude in the foothills (Talamau 47 m asl). Then the best temperature for parasitoid rearing was determined for the dominant parasitoid. A purposive sampling method was used for collecting the rice bug egg samples which were collected along 1 km transect lines in the rice fields. A descriptive method was used to report the parasitization levels. Rearing temperature treatments for the dominant rice bug egg parasitoids in the laboratory were 20oC, 25oC, 30oC and one batch raised as a control with no temperature regulation. 20 replications were conducted for each treatment. The data were analyzed using Completely Randomized Design (Statistics 8). The main species of rice bug egg parasitoids found were Hadronotus leptocorisae and Ooencyrtus malayensis with parasitization levels in the lowlands of 6.4% and 2.2% and the foothills of 28.4 % and 3.1% respectively. The best temperature for mass rearing parasitoid in the laboratory was 25oC, and they had the longevity of 22.6 ± 5.4 days.